Management of the child with allergy to non-antibiotic drugs - Bernardini, Roberto; Cardinale, Fabio; Mori, Francesca; Saretta, Francesca; Liotti, Lucia; Franceschini, Fabrizio; Crisafulli, Giuseppe; Caimmi, Silvia; Bottau, Paolo; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Non-steroidal anti-inflammatory drugs, perioperative drugs, radio contrast media and chemotherapeutics drugs are, after the non-antibiotic drugs, the drugs most commonly responsible for allergic reactions in children. Management is different depending on the drug involved.